Neuroprotective Effect of HIIT against GFAP Hypertrophy through Mitochondrial Dynamics in APP/PS1 Mice. (2nd February 2022) - Liu, Qianqian; Fu, Xiaonan; Han, Rui; Liu, Xuefeng; Zhao, Xiantao; Wei, Jianshe
Abstract : Alzheimer's disease (AD) is characterized by the accumulation of β -amyloid (A β ) plaques and tau neurofibrillary tangles in the brain. Although the exact details of the neuronal protective effect of high-intensity interval training (HIIT) on AD remain unclear, the preclinical phase of AD appears to be the important time point for such intervention. The described experiment investigates the neuroprotective effect of HIIT on AD in APP/PS1 mice. In total, 14 C57BL6 healthy control (C) mice and 14 APP/PS1 AD mice were each randomly assigned into two groups, one that did not participate in HIIT (C and AD groups, respectively) and the other subject to HIIT intervention (control HIIT (CE) and AD HIIT (ADE) groups, respectively). Visualization of hippocampal neuronal cells via HE and Congo red staining showed significant improvement in cell status and a significant reduction in amyloidosis in ADE compared with AD. The results of behavioral analysis show that the HIIT intervention significantly improved cognitive decline and reduced spatial exploration in both the C and AD groups. Immunofluorescence showed that the overall brain and the hippocampus of aged rats in the C and AD groups had different degrees of neuroglial responses and astrocyte GFAP proliferation and hypertrophy, with obvious improvement in the CE and ADE groups after 10 weeks of HIIT intervention. These results show that HIIT significantly improves the status of mitochondrial kinetic proteins and related proteins, with the mechanism differing between the normal aging C and the AD groups. 10 weeks of HIIT improved the imbalance in mitochondrial dynamics present in normal control mice and in AD mice. We conclude that preclinical training intervention has a significant positive effect on the exploratory behavior and cognitive functioning of mice.